The Effect of Myrmecodia pendans Ethanol Extract on Inflamed Pulp: Study on Sprague Dawley Rats - Janti Sudiono; Meylisa Hardina (Cell and BioPharmaceutical Institute, 2019)
Background: Inflammation is a body response caused by injury and infection. Pulpitis is a pulp tissue inflammation which is the continuous process of pulp hyperemia by bacteria invasion. Myrmecodia pendans or Sarang semut is known to contain flavonoid compound which has the anti inflammation effect. The purpose of this study is to investigate the effect of Myrmecodia pendans ethanol extract on the healing process of pulp inflammation.Materials and Methods: This experimental study involved pre- and post-in vivo treatment of 27 Sprague Dawley rats in which the inducted pulpitis model was obtained by injecting 0.01 mL Porphyromonas gingivalis into the dental pulp for 48 hours. Subjects were divided randomly into Group I (negative control), Group II (pulpitis treated by Myrmecodia pendans extract ethanol as treatment group), and Group III (pulpitis treated by Ca(OH)2 as positive control group). Group II and III as pulpitis treatment groups were divided into subgroups based on the induction periods of 48 hours (2 days), 168 hours (7 days), and 366 hours (14 days). All specimens were processed into the slides and evaluated microscopically for the healing process.Results: The result of this study showed significant difference (p<0.05) among groups on day 2, 4 and 7. On day 4, the pulpitis treatment group of Myrmecodia pendans extract showed better healing process than Ca(OH)2. On day 7, the pulpitis treatment group of Ca(OH)2 showed better healing process than Myrmecodia pendans extract. On day 14, both of the pulpitis treatment groups showed normal pulp.Conclusion: Myrmecodia pendans ethanol extract is effective for the healing process of inflamed pulp.Keywords: inflamed pulp, Myrmecodia pendans, sarang semut, Ca(OH)2 , healing process